Small Satellite Missions for Earth Observation New Developments and Trends - Sandau, Rainer; Roeser, Hans-Peter.; Valenzuela, Arnoldo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This book was compiled from those contributions given at the 7th IAA Symposium on Small Satellites for Earth Observation, May 4-8, 2009, Berlin (IAA – International Academy of Astronautics) which are representative for the new developments and trends in the area of small satellites for Earth observation. They reflect the potentials of a diversity of missions and related technologies. They may be based on national projects or international co-operations, single satellites of constellations, pico-, nano-, micro- or mini-satellites, developed by companies, research institutions or agencies. The main focus is on new missions to monitor our Earth’s resources (chapter 1), and the environment in which our Earth is embedded (chapter 2). Chapter 3 deals with distributed space systems, the unique feature of small satellites. The university satellites chapter (chapter 4) shows the high quality which is already reached by some of the universities worldwide. Chapter 5 gives insight into new developments in the fields of instruments and technologies. The last two chapters (chapters 6, 7) deal with subjects, necessary to make use of the data coming from the satellite systems: attitude and position.
New Earth Observation Missions -- Overview on CNES Micro Satellites Missions: In Flight, Under Development and Next -- Small Earth Observing Satellites Flying with Large Satellites in the A-Train -- INTA?Sat-1 First Earth Observation Mission -- VEN?S (Vegetation and Environment Monitoring on a New Micro Satellite) -- The “Ulingo” Mid-Low Latitudes Observation (MILO) Mission -- The Italian Precursor of an Operational Hyperspectral Imaging Mission -- Earth Environment Missions -- Space System “Radiomet” for GLONASS/GPS Navigation Signal Radio Occultation Monitoring of Lower Atmosphere and Ionosphere Based on Super-Small Satellites -- The Study of Electromagnetic Parameters of Space Weather, Micro-Satellite “Chibis-M” -- SEPSAT – A Nanosatellite to Observe Parameters of Space Weather -- Small Satellite Constellations for Measurements of the Near-Earth Space Environment -- Distributed Space Systems -- Satellite Formation for a Next Generation Gravimetry Mission -- EO Small Satellite Missions and Formation Flying -- Relative Trajectory Design for Bistatic SAR Missions -- Conceptual Design of the FAST-D Formation Flying Spacecraft -- Earth Observation Using Japanese/Canadian Formation Flying Nanosatellites -- A Bi/Multi-Static Microsatellite SAR Constellation -- Mission Design of the Dutch-Chinese FAST Micro-Satellite Mission -- University Satellites -- SPRITE-SAT: A University Small Satellite for Observation of High-Altitude Luminous Events -- SwissCube: The First Entirely-Built Swiss Student Satellite with an Earth Observation Payload -- German Russian Education Satellite – Mission Outline and Objectives -- University Microsatellites Equipped with an Optical System for Space Debris Monitoring -- A First-MOVE in Satellite Development at the TU-München -- Design of a Small Educational Satellite for the Italian High School Students: The EduSAT Project -- Testing of Critical Pico-Satellite Systems on the Sounding Rocket Rexus-4 -- Laboratory Facility for Simulation and Verification of Formation Motion Control Algorithms -- Asynchronous Parallel Reactive System for Intelligent Small Satellite on-Board Computing Systems -- NanoSiGN – Nanosatellite for scientific interpretation of GNSS dual-frequency signals in the low Earth orbit -- Instruments and Technologies -- The Vegetation Instrument for the PROBA-V Mission -- Software Defined LFM CW SAR Receiver for Microsatellites -- PhytoMapper – Compact Hyperspectral Wide Field of View Instrument -- Development of Spaceborne Small Hyperspectral sensor HSC-III for Micro Satellite -- Towards a Miniaturized Photon Counting Laser Altimeter and Stereoscopic Camera Instrument Suite for Microsatellites -- A Plan of Spaceborne ISAR Satellite Imaging System Aiming at Space Objects -- Increasing the Data Volume Returned from Small Satellites -- Integrated Design Based Plug-and-Play Small SAR Satellite Project -- Attitude Control Systems -- Star Sensor Development Based on the TUBSAT Experience -- Small Sensors Big Choices -- Robust and Fault Tolerant AOCS of the TET Satellite -- Implementation of the T3?PS in the Delfi-n3Xt Satellite -- A Novel AOCS Cold-Gas Micro-Propulsion System Design and Applications to Micro and Nano Satellites -- Navigation -- Navigation Needs for ESA’s Earth Observation Missions -- Benefits of Galileo for Future Satellite Missions -- Differential GPS: An Enabling Technology for Formation Flying Satellites -- GPS-Based Relative Navigation in Earth Observation Missions Relying on Cooperative Satellites.
Keywords: Remote sensing; Space sciences; Aerospace engineering; Astronautics; Remote Sensing/Photogrammetry.; Space Sciences (including Extraterrestrial Physics, Space Exploration and Astronautics).; Aerospace Technology and Astronautics